REVITALIZING ARABIC LANGUAGE LEARNING IN THE ERA OF 5.0: THE ROLE OF SOCIAL MEDIA IN BI'AH LUGHAWIYYAH - Rani, Samsuar A; Zikriati, Zikriati; Rosmiati, Rosmiati (Institut Agama Islam Negeri Lhokseumawe, 2024)
This study aims to investigate methods for revitalizing Arabic language learning in the 5.0 era, emphasizing the role of social media in enhancing students' educational experiences within the linguistic environment (Bi'ah Lughawiyyah). As digital technology becomes increasingly integrated into daily life, it is essential to adapt language learning strategies to leverage social media as an effective educational tool. Through a literature review approach, this research analyzes various studies on the use of social media in the context of Arabic language learning, considering contemporary theoretical concepts relevant to the 5.0 era. The findings are anticipated to offer new insights for educators in Arabic language education, facilitating the development of more relevant and effective learning strategies in this digital age.